Engineering and design design of coastal revetments, seawalls, and bulkheads. (EM (Series) (United States. Army. Corps of Engineers), 1995)
This manual applies to HQUSACE elements, major subordinate commands, districts, laboratories, and field operating activities having civil works responsibilities.